Deep Interior: Sensorial Encounters of Orang Suku Laut with the Sea - Suryantini, Rini; Saginatari, Diandra Pandu; Yatmo, Yandi Andri (Interiority, 2022)
This paper explores the idea of a deep interior during an encounter between a sea tribe and the sea, as an intimate interaction between the body and nature that consists of liquid matter, the earth’s surface, and the sea inhabitants. This paper introduces the idea of intimate engagement with such a liquid environment to reveal its interiorisation. It arguably positions ecological understanding through reading and responding to nature as the key to interiorisation. This study learns about the livelihood of a sea tribe, Orang Suku Laut (OSL), in the Riau Archipelago, Indonesia, mainly through food hunting and gathering activities. Through the trajectories produced during food-sourcing activities, it is revealed that reading and responding to nature depends on the multiple layers of nature’s dynamic entities: physical features, climatic conditions and particular signs. The deep interior suggests a different spatial understanding and ways of inhabiting the world, constructing an intimate interiorisation with ecology.